Justifying war propaganda, politics and the modern age - Welch, David; Fox, Jo (Palgrave Macmillan, 2012)
A new assessment of the debates about Just War in the twentieth and twenty-first centuries, from the imperial wars of the nineteenth century through the age of total war, the evolution of human rights discourse and international law, to proportionality during the Cold War and the redefinition of authority with the ascendancy of terror groups.